2018
DOI: 10.1136/postgradmedj-2017-135493
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure management in older people: balancing the risks

Abstract: Guidelines of arterial hypertension treatment based on individualised expected outcomes are not available for frail older persons. In this paper, we review the evidence, concerning management of arterial blood pressure (BP) in frail older patients. We focused on the best affordable methods for BP measurement; the age-related optimum BP; specific BP goals in agreement with the patients' general heath, frailty status, orthostatic and postprandial hypotension; balancing the benefits against risks of antihypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The blood pressure should be measured supine and after standing or sitting upright for 5 minutes. A decrease in systolic pressure of 20 mmHg or a decrease in diastolic pressure of 10 mmHg, especially when associated with dizziness or light-headedness, are consistent with the diagnosis of orthostatic hypotension [19]. Yet, bedbound persons might be unable to undergo a standard orthostatic test.…”
Section: Discussionmentioning
confidence: 88%
“…The blood pressure should be measured supine and after standing or sitting upright for 5 minutes. A decrease in systolic pressure of 20 mmHg or a decrease in diastolic pressure of 10 mmHg, especially when associated with dizziness or light-headedness, are consistent with the diagnosis of orthostatic hypotension [19]. Yet, bedbound persons might be unable to undergo a standard orthostatic test.…”
Section: Discussionmentioning
confidence: 88%
“…In this studies treatment of hypertension was found to be well The reviews from Correa A, et al [4] and Naschitz J, et al [5] refer that in frail elderly with multiple comorbidities an individualized approach should be considered and the therapeutic targets and regimes should consider risks in this population, such as possible secondary effects, potential drug interactions and that there may be a need for deintensification of antihypertensive treatment [6,7].…”
Section: Reviewmentioning
confidence: 99%
“…For example, dementia patients have a higher risk of hip fracture, a powerful determinant mortality in these patients [107], and antihypertensives represent a risk factor for fall injuries in advanced age [108]. Accordingly, older patients with cognitive decline might be the right target for the de-intensification clinical trials that have been proposed for antihypertensive treatment [109].…”
Section: Treatment Of Vascular Risk Factor: the Effect Of Aging And Cmentioning
confidence: 99%